Quantitative Easing in the Euro Area - An Event Study Approach - Florian Urbschat; Sebastian Watzka (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine the effects of the Asset Purchase Programme (APP) gradually introduced by the European Central Bank from September 2014 onwards. Studying the short-term reaction of financial markets after APP press releases, we analyse the development of bond yields and spreads around these releases. More precisely, we try to estimate different asset price channels by quantifying the cumulative decrease of spreads and by running event regressions for several Euro Area countries. Focusing on the signalling channel, measured by the OIS rate, and the portfolio rebalancing channel, proxied by the conditional bond-OIS spread, we find that the effects in yield and spread reduction were most pronounced for the initial announcement on the Public Sector Purchase Programme (PSPP) but declined afterwards for additional announcements. Possible explanations for this are the declining degree to which the ECB surprised markets and the increasingly burdensome institutional set-up of the APP. While yield reductions were larger for periphery countries' than for core countries' bonds, our evidence suggests that this stronger reduction is mostly due to a decreasing risk component of southern bonds. In fact, once controlling for this implicit credit risk reduction we find rather mild effects from portfolio rebalancing for all countries.
Keywords: E43; E44; E52; E58; G14; 330; large scale asset purchase; yield curve; quantitative easing; APP; event study